Evaluación de la psicomotricidad en niños y niñas en edad escolar residentes en el cantón Paquisha, expuestos ambientalmente a contaminación por metales pesados - Chamba Auquilla, Fernando Rodrigo (2015)
The present investigation has been raised based on the evaluation of the kids psychomotor abilities and their association with the presence of exhibition biomarkers; Describe the exhibition to heavy metals: Hg, Mn and Pb on the children school resident in the canton Paquisha; Describe the psychomotor development on the boys and girls in school age of the canton Paquisha. This investigation work is traverse type directed to children between 7 and 12 years of age resident in the canton Paquisha exposed to contamination on heavy metals. The study group got divided into three levels depending to the exhibition grade in which there in, we have; high, medium and low exhibition group. The evaluation was made to children that fulfilled the following requirements; been living in the sector during at least 6 previous months to the evaluation, been attending regularly to school, don’t have psychiatric problems, neurological or any type of disability that could affected its psychomotor development or any impediment to the realization of the test, for that reason three motor test were used: Finger Tapping that measures the coordination and speed motor, the Grooved Pegboard test that measures the kids’ manipulative dexterity and the Luria test that measures the individual's praxical capacities. The determination of the levels of Mn in hair, Pb in blood and Hg in urine was done by personal in the Laboratory of Chemical Analysis in the National University of Loja. Significant association was found among the punctuations of the Grooved Pegboard test and Luria regard to the biomarkers exposure, which determines that with the presence of metals, the abilities in the manipulative dexterity and the kids’ praxis are altered. While the motor coordination evaluated by the Finger Tapping test didn't show a significant relationship with any biomarker exposure. WORDS KEY: psychomotor abilities, biomarkers exposure, kids’, motor function, Mercury, Manganese, Lead.